Internalizing Honesty through Practical Habituation in Elementary Schools - Ahdiyat Hidayat; Ahmad Fatihul Ihsan; Mustakim Mustakim; Muhammad Tamamul Ma'arif; Achmad Abdul Munif (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
The crisis of self-control and the prevalence of academic dishonesty among elementary school-aged children in the digital era pose a crucial challenge for Islamic Education (PAI) teachers in formal public schools. This study aims to comprehensively analyze PAI teachers' strategies, supporting factors, and obstacles in fostering honest character among students at SDN Kayangan 1 Diwek Jombang. Utilizing a qualitative approach with a case study design, this field research was conducted intensively over three months. Primary data were gathered through in-depth interviews with five key informants, including the Headmaster, two PAI teachers, and two upper-grade student representatives, combined with passive participant observation and documentary studies. Data analysis applied the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing, while data trustworthiness was verified through source and technique triangulation. The findings demonstrate that nurturing an honest character in this public elementary school is systematically driven by integrating honesty indicators into the formal curriculum, standardizing cheat-free examinations, implementing Independent Worship Control Books, and encouraging social habituation through lost-and-found management. Active teacher involvement as behavioral role models (modelling) effectively accelerates the transformation of moral knowing into moral action. Despite facing obstacles from the negative influence of gadgets outside the school, the implementation of collaborative control mechanisms via WhatsApp Groups with parents and persuasive-restorative approaches successfully reduces children's behavioral deviation. This study concludes that the dialectic between school environment regulations (structural control) and exemplary teacher behavior (uswah hasanah) successfully transforms external control into internal control (self-control) in students from an early age